Peningkatan Keterampilan Berbicara dengan Pendekatan Komunikatif-Integratif di SMK Nusantara Plus Tangerang Selatan - Maulinda, Rerin (GERAM: Gerakan Aktif Menulis, 2021)
This study aims to improve students' speaking skills with a communicative-integrative approach at SMP Nusantara Plus Tangerang Selatan with the material of continuing the story. The subjects of this study were students of class 7A who were relevant to 30 people. The design in this research is classroom action research (classroom action research) which is conducted in three cycles. The data aids used are observation, interviews. The results of the study in cycles 1-3 said that the students' ability in speaking through the communicative-integrative approach had a significant increase. This increase can be seen based on the average value obtained when students carry out the teaching and learning process with the material continuing the story. In the first cycle, the number of students who told stories was 30 students with 70.55%. In the second cycle, 37 students who told stories had increased by 73.46%. In the third cycle, the number of students who told stories was 39 students with a percentage of 83.67%increased by 9.89%. The increase in speaking ability also increases with the increase in the average student activity during learning. The average student activity in cycle I was 65.30%. Student activity in cycle II had an increase of 9.48%, which was 75.77%, and activity in cycle III was 89.90%, which was an increase of 11, 65% of the average activity in cycle II. With the results obtained in each cycle, it is clear that they try to express their ideas and ideas when telling stories using communicative language and pay attention to linguistic and non-linguistic elements.